ANALISIS EFEKTIVITAS PAJAK PARKIR DAN RETRIBUSI PARKIR SEBAGAI SUMBER PENDAPATAN ASLI DAERAH KOTA PEKANBARU - Faradilla Sari; Putri, Annie Mustika; Puspita Sari, Dian Puji (Jurnal Akuntansi, Keuangan dan Teknologi Informasi Akuntansi, 2024)
Title of this research is Analysis of The Effectiveness of Parking Tax and Parking Retribution as Regional Revenue of Pekanbaru City. The aim of research is to determine the effectiveness of parking taxes and parking retribution and their contribution as regional revenue of Pekanbaru City. This research is a descriptive quantitative study. Using effectiveness analysis and contribution analysis to determine the level of effective and contribution of the two revenues. Based on data collection carried out by researchers through calculating the effectiveness and contribution of parking taxes and parking retribution, as well as interviews, calculation results that parking taxes and parking retribution less effective as regional revenue of Pekanbaru City. Meanwhile, the parking tax contribution have sufficient opportunities to contribute more as regional revenue of Pekanbaru City. Keywords: Parking Taxes, Parking Retribution, Original Local Government Revenue